Inhibition of High Substrate Concentration of Ammonia-Nitrogen in Bio-Filter - Kasmuri, Norhafezah; William Lovitt, Robert; ., . (International Journal of Engineering and Technology, 2018)
Nitrification process is very important to oxidize ammonia-nitrogen to nitrite-nitrogen and nitrate-nitrogen via ammonia oxidizing bacteria (AOB) and nitrite oxidizing bacteria (NOB). However, the high concentration of ammonia-nitrogen would inhibit the nitrification process. The presence of excessive ammonia-nitrogen would retard the ammonia oxidation by nitrifying bacteria. Hence, the aim of this research is to evaluate the biological process of AOB in different concentration of high concentration of ammonia-nitrogen (200 mg/L to 500 mg/L) on batch culture system using bio-filter. The result showed that the percentage removal rate at concentrations higher than 400 mg/L ammonia-nitrogen would reduce the ammonia oxidation of AOB. The decay rate, k, for the concentration of 500 mg/L ammonia-nitrogen was calculated as -0.055. This value was the highest decay rate compared to the other decay rates obtained from different concentrations of ammonia-nitrogen that were analyzed. It can be concluded that the AOB in bio-filter attached growth system can tolerate the ammonia-nitrogen up to 400 mg/L.Â Â
Keywords: ammonia-nitrogen; ammonia oxidizing bacteria; decay rate; inhibition; percentage removal.